Geographic variation of Trypanosoma cruzi Discrete Typing Units from the main vector Triatoma infestans at different scales - Fernandez, Maria del Pilar (2014)
tWe assessed the diversity and distribution of Trypanosoma cruzi discrete typing units (DTU) in Triatomainfestans populations and its association with local vector-borne transmission levels at various geographicscales. At a local scale, we found high predominance (92.4%) of TcVI over TcV in 68 microscope-positiveT. infestans collected in rural communities in Santiago del Estero province in northern Argentina. TcVwas more often found in communities with higher house infestation prevalence compatible with activevector-borne transmission. Humans and dogs were the main bloodmeal sources of the TcV- and TcVI-infected bugs. At a broader scale, the greatest variation in DTU diversity was found within the ArgentineChaco (227 microscope-positive bugs), mainly related to differences in equitability between TcVI and TcVamong study areas. At a country-wide level, a meta-analysis of published data revealed clear geographicvariations in the distribution of DTUs across countries. A correspondence analysis showed that DTUdistributions in domestic T. infestans were more similar within Argentina (dominated by TcVI) and withinBolivia (where TcI and TcV had similar relative frequencies), whereas large heterogeneity was foundwithin Chile. DTU diversity was lower in the western Argentine Chaco region and Paraguay (D = 0.14?0.22)than in the eastern Argentine Chaco, Bolivia and Chile (D = 0.20?0.68). Simultaneous DTU identificationsof T. cruzi-infected hosts and triatomines across areas differing in epidemiological status are needed toshed new light on the structure and dynamics of parasite transmission cycles.